The Ecology of Human Mobility. (March 2017) - Meekan, Mark G.; Duarte, Carlos M.; Fernández-Gracia, Juan; Thums, Michele; Sequeira, Ana M.M.; Harcourt, Rob; Eguíluz, Víctor M.
Abstract : Mobile phones and other geolocated devices have produced unprecedented volumes of data on human movement. Analysis of pooled individual human trajectories using big data approaches has revealed a wealth of emergent features that have ecological parallels in animals across a diverse array of phenomena including commuting, epidemics, the spread of innovations and culture, and collective behaviour. Movement ecology, which explores how animals cope with and optimize variability in resources, has the potential to provide a theoretical framework to aid an understanding of human mobility and its impacts on ecosystems. In turn, big data on human movement can be explored in the context of animal movement ecology to provide solutions for urgent conservation problems and management challenges. Trends: Near universal uptake of smartphones has moved human mobility research into big data. These data describe human mobility and behaviour with unprecedented resolution. Applying ecological theory provides a framework to inform and predict human mobility. Applications include but are not limited to epidemics, commuting, and crowd behaviour. In turn, big data on human movement can provide solutions for urgent conservation problems and management challenges.